Analysis of a nonlinear problem involving discrete and proportional delay with application to Houseflies model - Kamal Shah; Muhammad Sher; Muhammad Sarwar; Thabet Abdeljawad (AIMS Mathematics, 2024)
This manuscript established a comprehensive analysis of a general class of fractional order delay differential equations with Caputo-Fabrizio fractional derivative (CFFD). Functional analysis was used to examine the existence and uniqueness of the suggested class and to generate sufficient requirements for Ulam-Hyers (UH) type stability. Further, a numerical method based on Lagrange interpolation is used to compute approximate solution. Then, some applications in physical dynamics including a houseflies model and a Cauchy type problem were discussed to illustrate the established analysis with graphical illustrations.